Realizing Inter-Tribal Kinship through Martial Arts Performances in Indonesia: Historical Study of the Mamoncak Tradition - Windi Sekar Sari; Muhammad Faishal (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The Mamoncak tradition as martial art performances is one of the classic Malay traditions in Indonesia that still exists today. The existence of the tradition is supported by many factors that need to be explored. Thus the purpose of this article is to find out the history and development of the Mamoncak tradition in Silo Lama Village, Silau Laut District, Asahan, Indonesia. The research method used is qualitative research with a historical approach. Data collection was carried out by interviews and exploration of relevant scientific references both from books and relevant journal articles. The results of the research show that the Mamoncak tradition was first carried out by Sheikh Abdurrahman Silau Laut, a migrant who came from Tanjung Tiram Batubara, North Sumatra. The Mamoncak tradition was used as a condition for the opening of the new village “Silau Laut” based on an agreement between Sheikh Abdurrahman Silau Laut and the supernatural beings so that the two creatures live in harmony. This tradition continued to be carried out and financed by the local community from 1901 AD until 1999 AD. In the year 2000 AD this tradition became more existent because the government through the Department of Education and Culture and the Ikatan Pencak Silat Indonesia (IPSI) took part in promoting and financing the tradition. Political-social factors are identified as factors in the development of the Mamoncak tradition. The Reform era became the starting point for the government to care about the development of the tradition. On the other hand, the old order transmigration policy made the Mamoncak tradition known by various tribes in Indonesia. Thus the Mamoncak tradition has become a gathering place between martial arts schools, both from among the Malay tribe community and other tribe communities in Indonesia.